Astrocytic exportin‐7 responds to ischemia through mediating LKB1 translocation from the nucleus to the cytoplasm. Issue 2 (24th September 2014) - Liang, Hai Jie; Chai, Rui Chao; Li, Xi; Kong, Jin Ge; Jiang, Jiao Hua; Ma, Ju; Vatcher, Greg; Yu, Albert Cheung Hoi
<x xml:space="preserve">Abstract</x> The superfamily of importin‐β–related proteins is the largest class of nuclear transport receptors and can be generally divided into importins and exportins according to their transport directions. Eleven importins and seven exportins have been identified, and the expression patterns of both classes are important for their functions in nucleocytoplasmic transport activities. This study demonstrates that all of the importins (importin‐β; transportin‐1, ‐2, and ‐3; and importin‐4, ‐5, ‐7, ‐8, ‐9, ‐11, and ‐13) and all the exportins (exportin‐1, ‐2, ‐4, ‐5, ‐6, ‐7, and ‐t) are differentially expressed in the cerebral cortex, cerebellum, hippocampus, and brainstem and in primary cultures of cerebral cortical astrocytes and neurons. For astrocytes, we observed that different importins and exportins displayed different expression changes during 0–6 hr of ischemia treatment, especially an increase of both the mRNA and the protein of exportin‐7. Immunostaining showed that exportin‐7 accumulated inside the nucleus and around the nuclear envelope. In addition, we noticed an increased cytoplasmic distribution of one of the cargo proteins of exportin‐7, LKB1, an important element in maintaining energy homeostasis. This increased cytoplasmic distribution was accompanied by an increased expression of exportin‐7 under ischemia in astrocytes. We demonstrate that exportin‐7 responds to ischemia in astrocytes and that this response involves translocation of LKB1, a protein that plays important roles during metabolic stress, from the nucleus to the cytoplasm. © 2014 Wiley Periodicals, Inc.